Nine Things Genomics Can Tell Us About Candida auris - Chybowska, Aleksandra D.; Childers, Delma S.; Farrer, Rhys A. (Frontiers in Genetics, 2020)
Candida auris is a recently emerged multidrug-resistant fungal pathogen causing severe illness in hospitalised patients. C. auris is most closely related to a few environmental or rarely observed but cosmopolitan Candida species. However, C. auris is unique in the concern it is generating among public health agencies for its rapid emergence, difficulty to treat, and the likelihood for further and more extensive outbreaks and spread. To date, five geographically distributed and genetically divergent lineages have been identified, none of which includes isolates that were collected prior to 1996. Indeed, C. auris’ ecological niche(s) and emergence remain enigmatic, although a number of hypotheses have been proposed. Recent genomic and transcriptomic work has also identified a variety of gene and chromosomal features that may have conferred C. auris with several important clinical phenotypes including its drug-resistance and growth at high temperatures. In this review we discuss nine major lines of enquiry into C. auris that big-data technologies and analytical approaches are beginning to answer.